Validity Of Project Based Learning Model Integrated Sasambo Local Wisdom To Improve Students' Entrepreneurial Science Thinking - Rahman, Nanang; Nursina Sari; Liswijaya (Chemistry Education Department of Education and Teaching Faculty, 2024)
This study aims to develop a project based learning model integrated with Sasambo local wisdom to enhance entrepreneurial science thinking. The type of research conducted is developmental research. The subject of development research is the Sasambo integrated Project Based Learning (PjBL) model and its supporting devices, applied to students. The data collection method involved validating the model book and supporting instructional materials for model implementation. The validation was carried out by three science education experts who evaluated the model book, semester learning plans, lecture session plan, student activity sheets, and the assessment sheets for entrepreneurial science thinking. The research findings indicate that the project based learning model integrated with Sasambo local wisdom shows excellent relevance and consistency, with criteria that are highly valid and reliable. The project based learning model integrated with Sasambo local wisdom consists of six stages: (1) project orientation, (2) problem identification within groups, (3) information gathering, (4) project design, (5) project implementation, and (6) presentation and evaluation. The developed model can effectively train entrepreneurial science thinking, as the learning stages are already integrated with the indicators of entrepreneurial science thinking.